An Integrated theory of false insights and beliefs under psychedelics - H. T. McGovern; H. J. Grimmer; M. K. Doss; B. T. Hutchinson; C. Timmermann; A. Lyon; P. R. Corlett; R. E. Laukkonen (Communications Psychology, 2024)
Abstract Psychedelics are recognised for their potential to re-orient beliefs. We propose a model of how psychedelics can, in some cases, lead to false insights and thus false beliefs. We first review experimental work on laboratory-based false insights and false memories. We then connect this to insights and belief formation under psychedelics using the active inference framework. We propose that subjective and brain-based alterations caused by psychedelics increases the quantity and subjective intensity of insights and thence beliefs, including false ones. We offer directions for future research in minimising the risk of false and potentially harmful beliefs arising from psychedelics. Ultimately, knowing how psychedelics may facilitate false insights and beliefs is crucial if we are to optimally leverage their therapeutic potential.